Effect of Emotional Intelligence on Employee Performance in Gen Z - Ekasari, Silvia; Haji, Wachyu Hari; Ishak, Olfin; Nurdiani, Tanti Widia; Wulansari, Murwani (LPPPIPublishing, 2024)
This research aims to analyze effect of emotional intelligence on employee performance in Gen Z. This sort of investigate is affiliated investigate. The population in this study is Gen Z who are working in Indonesia. Based on these considerations, the number of research samples is 100 Gen Z who are working in Indonesia. Data analysis in this study using simple regression analysis. The results show that emotional intelligence has significant effect on employee performance in Gen Z.